Impact of Public Health Responses During a Measles Outbreak in an Amish Community in Ohio: Modeling the Dynamics of Transmission. Issue 9 (7th April 2018) - Gastañaduy, Paul A; Funk, Sebastian; Paul, Prabasaj; Tatham, Lilith; Fisher, Nicholas; Budd, Jeremy; Fowler, Brian; de Fijter, Sietske; DiOrio, Mary; Wallace, Gregory S; Grenfell, Bryan
Abstract: We quantified measles transmissibility during a measles outbreak in Ohio in 2014 to evaluate the impact of public health responses. Case incidence and the serial interval (time between symptom onset in primary cases and secondary cases) were used to assess trends in the effective reproduction number R (the average number of secondary cases generated per case). A mathematical model was parameterized using early R values to determine the size and duration of the outbreak that would have occurred if containment measures had not been initiated, as well as the impact of vaccination. As containment started, we found a 4-fold decline in R (from approximately 4 to 1) over the course of 2 weeks and maintenance of R < 1 as control measures continued. Under a conservative scenario, the model estimated 8, 472 cases (90% confidence interval (CI): 8, 447, 8, 489) over 195 days (90% CI: 179, 223) without control efforts and 715 cases (90% CI: 103, 1, 338) over 128 days (90% CI: 117, 139) when vaccination was included; 7, 757 fewer cases (90% CI: 7, 130, 8, 365) and 67 fewer outbreak days (90% CI: 48, 98) were attributed to vaccination. Vaccination may not account entirely for transmission reductions, suggesting that changes in community behavior (social distancing) and other control efforts (isolation, quarantining) are important. Our findings highlight the benefits of measles outbreak response and of understanding behavior change dynamics.